1999
DOI: 10.1111/1468-5957.00294
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Reorganizations: Changes in the Intensity of Labor and Capital Expenditures

Abstract: Using a new measure that indirectly captures a firm's restructuring efforts on the basis of changes in its labor and capital expenditure patterns, this study examines the link between restructuring and financial performance for an international sample of firms during the years 1989-1997. Results show that firms that curbed the growth in labor expense intensity (labor expense relative to sales), regardless of the accompanying changes in sales or in capital expenditure intensity, had significantly higher annual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 9 publications
(14 reference statements)
2
17
1
Order By: Relevance
“…Myopia is not present. Our findings are the opposite of Ballester, Livnat and Sinha's (1999). Their work suggests that the markets are negative about new labour investments, believing that directors are more interested in empire-building than profits.…”
Section: Discussioncontrasting
confidence: 60%
“…Myopia is not present. Our findings are the opposite of Ballester, Livnat and Sinha's (1999). Their work suggests that the markets are negative about new labour investments, believing that directors are more interested in empire-building than profits.…”
Section: Discussioncontrasting
confidence: 60%
“…That growth firms are less prone to downsize their workforce is largely consistent with the findings of Ballester, Livnat, and Sinha (1999). Growth firms, on the other hand, are increasing their combined workforce in all of the years investigated.…”
Section: (Ii) Return On Human Capital and Stock Returnssupporting
confidence: 78%
“…Revenue refocusing downsizing strategies are more successful than cost cutting and plant closing downsizing strategies. These findings help to clarify the apparent contradiction between ongoing corporate downsizing and the generally inconclusive empirical evidence to date with respect to both market reactions to layoff announcements and subsequent financial performance (Ballester et al, 1999;Cascio et al, 1997;Lee, 1997;Mentzer, 1996;and Worrell et al, 1991). Our results suggest that layoff announcements that disclose strategic plans for refocusing lines of business result in significantly positive abnormal market returns.…”
Section: Discussionmentioning
confidence: 53%
“…downsizing announcements. More recently, Ballester et al (1999) found evidence that firms that downsized employees while increasing capital expenditures did improve their financial performance. Given continued corporate downsizing and anecdotal reports of productivity gains associated with layoffs in the financial press, both the negative market reactions to downsizing announcements and the mixed financial performance results are puzzling.…”
mentioning
confidence: 99%